2021
DOI: 10.3390/nano11071828
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Cytocompatibility, and Biocompatibility of a Bioactive Glass Based Retrograde Filling Material

Abstract: The ideal retrograde filling material that is easy to handle, has good physicochemical properties, and is biocompatible has not yet been developed. The current study reports the development of a novel bioactive glass based powder for use as a retrograde filling material that is capable of altering the consistency and hardening rate of mixtures when mixed with existing bioactive glass based cement. Furthermore, its physicochemical properties, in vitro effects on human cementoblast-like cells, and in vivo effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…These findings indicated that both F-NBG and P-NBG formed apatite tested media, although only a scant amount of apatite was formed on F-NBG in 1 BSA-SBF. The positive AFA values of NBGs in SBF [3,10,11] and the negative effe BSA on apatite formation [14,15] are consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings indicated that both F-NBG and P-NBG formed apatite tested media, although only a scant amount of apatite was formed on F-NBG in 1 BSA-SBF. The positive AFA values of NBGs in SBF [3,10,11] and the negative effe BSA on apatite formation [14,15] are consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The present study has demonstrated that BG-based powder not only changes the consistency of NBG but also improves the AFA level. Moreover, a previous study reported that BG-based powder did not affect the solubility or cytocompatibility of NBG [11]. Based on these findings, it can be speculated that BG-based powder may be helpful in changing the consistency of other BG-based or non-BG-based endodontic materials, improving the AFA level.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The success of surgical endodontic treatment requires root-end filling materials that are easy to use, biocompatible, stable and economical [ 1 , 2 , 3 ]. The goal is to seal the apex hermetically and prevent microorganisms from entering the root canal [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the critical characteristics of ideal retrograde filling material is enough apical seal supply to prevent leakage of intra-channel stimulants into the apical peripheral tissue (13). Therefore, in the current study, we tried to compare the curative effect of different retrograde filling materials, i.e.…”
Section: Introductionmentioning
confidence: 99%